Two views on institutions and development: The grand transition vs. the primacy of institutions - Martin Paldam; Erich Gundlach (Kiel Institute for the World Economy (IfW), 2007)
The Grand Transition (GT) view claims that economic development is causal to institutional development, and that many institutional changes can be understood as transitions occurring at roughly the same level (zones) of development. The Primacy of Institutions (PoI) view claims that economic development is a consequence of an exogenous selection of institutions. Our survey of the empirical evidence and our own estimates reveal that it is easy to find con-vincing evidence supporting either of the two views. Property rights do affect development as suggested by the PoI. However, democracy is mainly an effect of development as suggested by the GT. We conclude that the empirical results are far too mixed to allow for a robust assessment that one of the two views is true and the other false. This finding implies that focusing on institutional development is unlikely to be successful as the key strategy for the economic development of poor countries.
Keywords: O1; B25; 330; Primacy of institutions; Democracy; Corruption; Development; Grand transition; Entwicklung; Institutionalismus; Eigentumsrecht; Demokratie; Schätzung; Welt; Entwicklungsländer